Software Product Management and Pricing - Kittlaus, Hans-Bernd (Springer, 2017)
Software product management and pricing are key success factors for any organization providing software, be it a software company or an organization responsible for software in a company that belongs to a different industry. After defining the term "software product" and looking at the business and organizational sides, the core elements of software product management and pricing are discussed. Recommendations are given on how to deal with these elements depending on different types of organizations and products in order to achieve the long-term success.